Uji Kinerja Lima Galur Jagung Hibrida Polinela Dibandingkan Dengan Lima Varietas Jagung Hibrida Unggul Nasional - Syuriani, Eka Erlinda; Putri, Ria; Hidayatullah Zaini, Akbar; Indrani, Satria Bagas; Krisnandar, Krisnandar (Jurnal Penelitian Pertanian Terapan, 2025)
Issues surrounding hybrid corn seeds in Indonesia include the increasing demand for seeds from year to year and the limited selection of hybrid varieties on the market. One solution to reduce the problem of hybrid corn seed availability is to develop new strains or varieties using parent plants from local areas. Polinela corn breeders have currently developed several hybrid corn lines (F1) that need to be tested for performance. The objective of this study was to determine the performance advantages of five Polinela hybrid corn lines compared to five superior commercial hybrid corn varieties developed by several multinational companies. The study was designed using a completely randomized block design (CRBD). The treatments used were five Polinela hybrid corn lines and five commercial hybrid corn varieties. The observations included quantitative yield components and yield potential, as well as several qualitative characteristics of the lines and varieties. The results showed that there were three new hybrid lines, namely line PL 401/PL 20, line PL.401/PL.2020, and line PL 202/PL 40), which had yield potential equivalent to the hybrid varieties BISI 18, NK 22, and Pertiwi 3, with a dry grain yield potential of between 11.7 and 12.9 tons.ha-1. There are three new hybrid corn lines with grain yield potential equivalent to three commercial varieties and higher than two comparison varieties, namely Pioneer 88 and Pertiwi 6.